Legal Protection For Doctors In Doing Medical Activities Related To The Distribution Of False Vaccine In Semarang District - Totok Sumariyanto; Trihoni Nalesti Dewi; Tjahjono Tjahjono (SOEPRA, 2018)
The case of the false vaccine circulation that occurred in Indonesia in mid-2016 had horrendous World Health and raising fears in society. This case raises the impact on doctors who provide vaccine or immunization to the patient. Due to the false vaccine case resulted in lowered public confidence towards the world of health, especially do immunization in toddlers. Concerns also arise on a doctor who gave the vaccine, because his own doctors did not know whether the vaccine will be given to the patient's original or false. It is interesting to be researched by the author to know about circulation and surveillance of vaccine in the area of Semarang. The research method used in this thesis is sociological juridical. Data collection was done with primary and secondary data that were gathered by interviews with some resources, such as Head of BPOM Central Java, Chairman IDI Semarang District, Head of District Health Office of Semarang, Pharmaceutical procurement department in Semarang District Hospital, doctor of RSUD Kabupaten Semarang who do the vaccine directly to patients, as well as library studies and related documents. This research is done explanatively. The result of the research, it can be concluded that the regulation concerning the circulation of drugs or vaccine in Indonesia is adequate. The process of circulation and procurement of vaccines in the district of Semarang on RSUD Ambarawa and RSUD Ungaran have been conducted in accordance with the procedures, including also in the implementation of the procurement of the vaccine so well controlled. Responsibility for the false vaccine relief in Indonesia is the responsibility of BPOM and the Health Department.  The circulation of drugs or vaccines may not be able to circulate in the community in a strict supervision and control and periodically by BPOM and the health service is running properly